2023
DOI: 10.3389/fimmu.2023.1130821
|View full text |Cite
|
Sign up to set email alerts
|

Association of SARS-CoV-2 nucleocapsid viral antigen and the receptor for advanced glycation end products with development of severe disease in patients presenting to the emergency department with COVID-19

Abstract: IntroductionThere remains a need to better identify patients at highest risk for developing severe Coronavirus Disease 2019 (COVID-19) as additional waves of the pandemic continue to impact hospital systems. We sought to characterize the association of receptor for advanced glycation end products (RAGE), SARS-CoV-2 nucleocapsid viral antigen, and a panel of thromboinflammatory biomarkers with development of severe disease in patients presenting to the emergency department with symptomatic COVID-19.MethodsBlood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Furthermore, Matthay et al. found that high levels of N protein and RAGE at admission were significantly correlated with the development of severe COVID-19 ( 111 ).…”
Section: Structural Protein-evoked Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Matthay et al. found that high levels of N protein and RAGE at admission were significantly correlated with the development of severe COVID-19 ( 111 ).…”
Section: Structural Protein-evoked Lung Injurymentioning
confidence: 99%
“…Wick et al demonstrated that N protein levels of plasma samples harvested within 72 h of hospital admission were strongly associated with RAGE and correlated with ICU admission as well as mechanical ventilation at 28 days (110). Furthermore, Matthay et al found that high levels of N protein and RAGE at admission were significantly correlated with the development of severe COVID-19 (111).…”
Section: N Proteinmentioning
confidence: 99%